A RESEARCH ON LABOR FORCE REQUİREMENT IN TURKİSH READY-WEAR INDUSTRY - (:unkn) unknown (My University, 2018)
Today, the Turkish ready-wear industry is undergoing a transformation process from acontract manufacturing to full package manufacturing. The most important input in theproduction of ready-wear is undoubtedly the labor force. For this reason, the success of thetransformation process is possible by meeting the qualified personnel needs of the industry. Inthis study, labor force requirement of the Turkish ready-wear industry is examined. Qualitativeresearch method is used in this study. Job adverts on ready-wear industry are investigated onwww.kariyer.net which is Turkey’s largest human resources website. Firstly the job positionswhich are most needed by the ready-wear industry and then the characteristics required forcandidates for these positions are determined. The obtained data are subjected to frequencyand percentage analyzes in the SPSS 21.0 program. According to the result of the research; themost needed personnel positions of Turkish ready-wear enterprises are "stylist", "merchandiser"and "sales consultancy" respectively. It has also been found that ready-wear enterprises areprimarily seeking communication skills and suitability for teamwork from the personnel who willwork in these positions. The main problem for ready-wear enterprises is to meet the need forpersonnel from outside the production area such as merchandiser, sales consultant, becauseenterprises request professional knowledge as well as marketing knowledge frommerchandisers and sales consultants. However, the marketing knowledge is given in themarketing programs and the professional knowledge is given in the professional departments inTurkey. This situation leads to the loss of time and money since firms have to give profesionaltranings to the marketing graduates for merchandiser position. The opposite of this case is alsotrue; the staff with professional knowledge also needs marketing knowledge. Therefore, theready-wear enterprises need vocational training education institutions which give bothmarketing and profession training to meet the labor force requirements of sales representativesand sales consultants. Because, in all the researches and studies carried out, it is emphasizedthat the contribution of education is important and the quality of labor force should be improvedthrough education.

Günümüz Türk hazır giyim sektörü, fason üretici bir sektörden tasarım ve moda üretici sektöre doğru bir dönüşüm süreci geçirmektedir. Hazır giyim üretiminde en önemli girdi hiç şüphesiz işgücüdür. Bu nedenle dönüşüm sürecinin başarılı olabilmesi, sektörün kalifiye eleman ihtiyacının karşılanmasıyla mümkün olacaktır. Bu çalışmada, Türk hazır giyim sektörünün işgücü ihtiyacı incelenmektedir. Bu çalışmada nitel araştırma yöntemi kullanılmaktadır. Türkiye'nin en büyük insan kaynağı sitesi olan www.kariyer.net adresinde hazır giyim sektöründeki iş ilanları incelenmiştir. Öncelikle hazır giyim sektörünün en çok ihtiyaç duyduğu iş pozisyonları ve daha sonra bu pozisyonlar için adaylarda aranan özellikler belirlenmiştir. Elde edilen veriler SPSS 21.0 programında frekans ve yüzde analizlerine tabi tutulmuştur. Araştırmanın sonucuna göre; Türk hazır giyim işletmelerinin en fazla ihtiyaç duydukları personel pozisyonları sırasıyla “modelistlik”, “müşteri temsilciliği” ve “satış danışmanlığı” dır. Ayrıca hazır giyim işletmelerinin bu pozisyonlarda çalışacak personellerden iletişim yeteneği ve takım çalışmasına uygun olma özelliklerini öncelikli olarak aradıkları sonucuna ulaşılmıştır. Hazır giyim işletmeleri için asıl sorun müşteri temsilcisi, satış danışmanı gibi üretimin dışındaki alanlardaki personel ihtiyacının karşılanmasıdır. Çünkü işletmeler, müşteri temsilcisi ve satış danışmanlarından, pazarlama bilgisinin yanında mesleki bilgi de aramaktadır. Ancak Türkiye’de pazarlama bilgisi pazarlama programlarında, mesleki bilgi ise mesleki bölümlerde verilmektedir. Bu durum hazır giyim işletmelerinin pazarlama mezunu bir personeli müşteri temsilcisi olarak işe aldığında, personele mesleki bilgi vermek zorunda kalmasına, para ve zaman kaybetmesine neden olmaktadır. Bu durumun tam tersi de doğrudur; meslek bilgisine sahip olan personelin de pazarlama bilgisine ihtiyacı olmaktadır. Bu nedenle hazır giyim işletmelerinin müşteri temsilcisi ve satış danışmanı işgücü ihtiyacının karşılanması için hem pazarlama hem de meslek eğitimi veren eğitim kurumlara ihtiyaç duyulmaktadır. Çünkü yapılan tüm araştırma ve incelemelerde, eğitimin katkısının önemli olduğu, işgücünün eğitim yoluyla kalitesinin iyileştirilmesi gerektiği vurgulanmaktadır.
TÜRK HAZIR GİYİM SEKTÖRÜNDE İŞGÜCÜ İHTİYACI ÜZERİNE BİR ARAŞTIRMA
Keywords: Tarih